Analisis Kemampuan Argumentasi Siswa SMA pada Topik Usaha dan Energi - Ayu Nur'aini, Devi; Sinaga, Parlindungan (Experiment: Journal of Science Education, 2025)
Argumentation skills related to critical thinking skills that are important for 21st century students. This study aims to identify differences argumentation skills based on gender of senior high school students in Tangerang Regency. This research method is quantitative descriptive utilizing a sample of 110 high school students consisting of 44 male students and 66 female students. The sample was utilized purposive sampling technique. The research instrument consisted of 8 essay items on the topic Works and Energy with a reliability coefficient α=0,778. The argumentation components that were measured are claims, warrant, backing, and rebuttal. The results of this study showed that 19% answers of students were only claims, 81% answers of students were warrant and backing, and 11% answers of students were rebuttal. The results of the Mann Whitney test were no differences the argumentation skill among male and female students. However, male students have a slightly higher skill to make either weak rebuttal or identifiable rebuttal.